2017
DOI: 10.1080/03079457.2016.1268675
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bronchitis vaccine virus detection and part-S1 genetic variation following single or dual inoculation in broiler chicks

Abstract: An investigation was undertaken of the extent of genetic variation occurring within infectious bronchitis virus (IBV) vaccine strains following vaccination of day-old broiler chicks. Chicks were divided into seven groups, with two groups receiving single Massachusetts (Mass) vaccinations while the other four were inoculated with combinations of different IBV serotypes; Mass, 793B, D274 and Arkansas (Ark). The remaining group was maintained as an unvaccinated control. Following vaccination, swabs and tissues co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…With both experiments, Sanger sequencing showed that the genotype of strains recovered using OP swabs altered from Mass to 793B after 14 dpv. As reported previously [26,27], while the Mass genotype made up the majority of detections during early sampling days (3-14 dpv), the 793B strain became the dominant strain by 21 dpv. The reason for the shifting of genotypes from Mass to 793B is not known, however, previous work has highlighted that different IBV strains can differentially induce host expression pathways, in particular TLR7 [65] and IFN-b [66].…”
Section: Ibv Ampvsupporting
confidence: 82%
See 4 more Smart Citations
“…With both experiments, Sanger sequencing showed that the genotype of strains recovered using OP swabs altered from Mass to 793B after 14 dpv. As reported previously [26,27], while the Mass genotype made up the majority of detections during early sampling days (3-14 dpv), the 793B strain became the dominant strain by 21 dpv. The reason for the shifting of genotypes from Mass to 793B is not known, however, previous work has highlighted that different IBV strains can differentially induce host expression pathways, in particular TLR7 [65] and IFN-b [66].…”
Section: Ibv Ampvsupporting
confidence: 82%
“…IBV vaccinal strains have previously been shown to persist in chickens for a longer period [53,63]. To further investigate this, the growth kinetics and genetic characteristics of live IBV vaccines used in this study were cross compared with previous reports [26,64]. Vaccinal strains were detected in OP swabs throughout the current experiment, with the variant 793B strain dominating at the later ages of the birds.…”
Section: Ibv Ampvmentioning
confidence: 85%
See 3 more Smart Citations